(Pro)renin Receptor Regulates Phosphate Homeostasis in Rats via Releasing Fibroblast Growth Factor-23 - Lu, Aihua; Pu, Min; Mo, Shiqi; Su, Jiahui; Hu, Jiajia; Li, Chunling; Wang, Weidong; Yang, Tianxin (Frontiers in Physiology, 2022)
Phosphate (Pi) is one of the basic necessities required for sustenance of life and its metabolism largely relies on excretory function of the kidney, a process chiefly under the endocrine control of bone-derived fibroblast growth factor 23 (FGF23). However, knowledge gap exists in understanding the regulatory loop responsible for eliciting phophaturic response to Pi treatment. Here, we reported a novel role of (pro)renin receptor (PRR) in mediating phosphaturic response to Pi treatment via upregulation of FGF23 production. Male Sprague-Dawley rats were pretreated for 5 days via osmotic pump-driven infusion of a PRR antagonist PRO20 or vehicle, and then treated with high Pi (HP) solution as drinking fluid for the last 24 hours. PRO20 reduced HP-induced Pi excretion by 42%, accompanied by blunted upregulation of circulating FGF23 and parathyroid hormone (PTH) and downregulation of renal Na/Pi-IIa expression. In cultured osteoblast cells, exposure to HP induced a 1.56-fold increase in FGF23 expression, which was blunted by PRO20 or siRNA against PRR. Together, these results suggest that activation of PRR promotes phosphaturic response through stimulation of FGF23 production and subsequent downregulation of renal Na/Pi-IIa expression.